Portrait of a Chemistry Teacher’s Efforts in Creating an Inclusive Classroom - Fauzan Abrori; Jamil Suprihatiningrum (Proceeding International Conference on Religion, Science and Education, 2023)
High school chemistry teachers in the Special Region of Yogyakarta can use this research as a source of information and a reference for developing curriculum implementation, learning strategies, and inclusive classroom assessments. and as input for the development and improvement of inclusive education programs for Yogyakarta equivalent high schools, especially in other districts that want to realize inclusive classes in general. This research study uses a qualitative descriptive method to describe the experience of teaching the object under study. that the percentage of learning strategies for teaching students with disabilities in the application of inclusive chemistry classes that were agreed upon with an average of 79% had the highest percentage, disagreed with 13%, and doubted 8%. For the percentage of learning strategies for teaching students with disabilities in the application of inclusive chemistry classes, agreement with an average of 85% has the highest percentage, disagreement is 7%, and doubt is 7%. And the percentage of learning development monitoring and assessment techniques for persons with disabilities in the application of the inclusion chemistry class agreed, with an average of 86% having the highest percentage, 11% disagreeing, and 4% unsure.